PERBAIKAN LINI PRODUKSI DENGAN PERANCANGAN MODEL SIMULASI UNTUK MENGURANGI OVERTIME DI PT.EBARA INDONESIA - Sucipto Adisuwiryo; Parwadi Moengin; Obriga Nathaniel Menayang (JURNAL TEKNIK INDUSTRI, 2015)
PT Ebara Indonesia is a company that manufactures centrifugal pump. One of the type thatthe company makes is the FS Pump. These pumps are getting requests from customers who requirethese products produced faster. The problems that arise on the production floor is the imbalance ofproduction line which causes additional work time. The goal is to reduce overtime on the productionfloor.The study was conducted by calculating the operator utilization and TOC using the dataprocessing time from 10 observations as input, in which uniformity and adequacy of the data has beentested. After calculation, it is known that the sandblast and inspection work station requires one moreoperator. Production time in the simulation will be used as an indicator in validation.Simulation approach is done by making the initial model representing the real situation. Thenthe model will be verified, validated and replicated. After that, experiments will be made to achieve thegoal. Then from those experiment, the best scenario was obtained. The best scenario proposed thatsandblasting and inspection operator increase by one and one sand mold BC operator was moved.Completion time obtained was reduced from 506.66 hours to 344.07 hours, so there is no overtimeneeded.